Analysis of Learning Motivation of Gifted and Talented Children: an Islamic Perspective - Viana, Shef; Syafril, Syafrimen; Yusof, Rorlinda (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
Learning motivation is influenced by intrinsic and extrinsic factors; gifted children quickly get bored with activities that do not match their abilities and need higher challenges to stay motivated. This study used the systematic literature review (SLR) method. Data collection used literature studies. The number of analyzed documents was 25 from highly reputable journals (Q1, Q2, Q3, Q4 and Sinta 2) obtained through Scopus, Springer, Eric, Sciendirect, Doaj, Taylor, and Google Scholar. The data were analyzed using Miles and Huberman's interactive qualitative analysis with the help of NVIVO software 12. The study results showed that the intrinsic learning motivation of gifted and talented children was more dominant than the extrinsic one. It includes liking challenges, high curiosity, creativity and innovation, and liking exploration. Strong learning motivation in gifted and talented children aligns substantially with Islamic values. The encouragement to continue learning, exploring knowledge, innovating, and exploring one's potential is an integral part of the implementation of Allah's command to seek knowledge and utilize the intellect that He has given. This not only contributes to the achievement of academic and professional success but also deepens their faith and piety in God Almighty. This research could contribute to understanding learning motivation from the Islamic perspective and increase the learning motivation of gifted and talented children based on Islamic teachings.